Persistent Diarrhoea after Percutaneous Endoscopic Gastrostomy (PEG) in Paediatric Patient: Lessons from a Complication - Sara Silvaroli; Filomena Valentina Paradiso; Valentina Giorgio; Lorenzo Nanni (Hindawi Limited, 2022)
Percutaneous endoscopic gastrostomy (PEG) is increasingly used in paediatric population. We report a case of a 4-year-old boy who, two weeks after PEG placement, presented persistent diarrhoea interpreted as intolerance to enteral feeding. His CT scan confirmed the correct placement of gastrostomy, but during gastroscopy, gastrostomy could not be found in the stomach, and the following colonoscopy revealed migration of gastrostomy to the transverse colon. The patient required removal of the misplaced PEG and conservative management of the fistula with surgical replacement of gastrostomy. We faced an unusual presentation of PEG placement complication due to colon interposition during blind gastric puncture. In children with anatomical deformities, previous surgery, or low weight or malnutrition (<10 kg), we suggest laparoscopic-assisted gastrostomy to avoid the risk of a major complication.